DI-010 Factors influencing the appearance of haematological and thyroid adverse effects in patients with hepatitis C virus genotype 1 treated with telaprevir/boceprevir plus peg-interferon and ribavirin. (24th March 2015) - Manzaneque, A; Sotoca, JM; Lens, S; Kostov, B; Codina, C
Abstract : Background: Telaprevir (TVR) or boceprevir (BOC) with peg-interferon/ribavirin (PR) to treat HCV genotype 1 is associated with haematological adverse effects like anaemia, neutropenia or thrombocytopenia and alterations in thyroid function. Factors influencing the appearance of these adverse effects remain undefined. Purpose: We aimed to assess the relationship between the characteristics of our population undergoing triple therapy (TT) and those adverse events. Material and methods: 61 patients with hepatitis C genotype 1 treated with triple therapy (TT) during the period between January 2012 to June 2014 were included. We collected demographic data (age, sex), HCV genotype 1 (1a, 1b), fibrosis stage at the beginning of treatment (Metavir score) and TT treatment with TVR or BOC. The adverse effects analysed were: anaemia, thrombocytopenia, decreased granulocyte count and hypothyroidism/hyperthyroidism. Fisher exact test was used to study the associations between adverse effects and factors corresponding to patients' characteristics. Statistical analysis were conducted using the statistical software R. Results: The characteristics of the patients were: 47 men (14 woman), mean age 57 ± 9.3 years, 49 genotype 1b, 53 patients in TT with TVR (9 BOC) and 55 patients fibrosis stage F3–F4. Anaemia (haemoglobin ≤ 10 g/dL) appeared in 29 (47.5%) patients. Neutropenia (granulocytes ≤ 0.75 × 10 9 /L) appeared in 15 (24.6%) patients. Thrombocytopenia (platelet count ≤ 0.50 × 10 9 /L) appeared in 5 (8.2%) patients. Hyper or Hypothyroidism (THS levels ≤ 0.4 or ≥ 4 mIU/mL respectively) appeared in 18 (29.5%) patients. Only statistically significant relationship was observed between age and anaemia (p = 0.013). Conclusion: Age and not fibrosis stage was the main factor associated to the development of anaemia during triple therapy. References: D'Ambrosio R, Colombo M. Dig Liver Dis; 2013;45(Suppl 5):S363–6 Hézode C, et al . Gastroenterology 2014;147 No conflict of interest.